Biotinylation as a tool to enhance the uptake of small molecules in Gram-negative bacteria - Pandeya, Ankit; Yang, Ling; Alegun, Olaniyi; Karunasena, Chamikara; Risko, Chad; Li, Zhenyu; Wei, Yinan (PLOS ONE, 2021)
Antibiotic resistance is a major public health concern. The shrinking selection of effective antibiotics and lack of new development is making the situation worse. Gram-negative bacteria more specifically pose serious threat because of their double layered cell envelope and effective efflux systems, which is a challenge for drugs to penetrate. One promising approach to breach this barrier is the “Trojan horse strategy”. In this technique, an antibiotic molecule is conjugated with a nutrient molecule that helps the antibiotic to enter the cell through dedicated transporters for the nutrient. Here, we explored the approach using biotin conjugation with a florescent molecule Atto565 to determine if biotinylation enhances accumulation. Biotin is an essential vitamin for bacteria and is obtained through either synthesis or uptake from the environment. We found that biotinylation enhanced accumulation of Atto565 in E. coli. However, the enhancement did not seem to be due to uptake through biotin transporters since the presence of free biotin had no observable impact on accumulation. Accumulated compound was mostly in the periplasm, as determined by cell fractionation studies. This was further confirmed through the observation that expression of streptavidin in the periplasm specifically enhanced the accumulation of biotinylated Atto565. This enhancement was not observed when streptavidin was expressed in the cytoplasm indicating no significant distribution of the compound inside the cytoplasm. Using gene knockout strains, plasmid complementation and mutagenesis studies we demonstrated that biotinylation made the compound a better passenger through OmpC, an outer membrane porin. Density functional theory (DFT)-based evaluation of the three-dimensional geometries showed that biotinylation did not directly stabilize the conformation of the compound to make it favorable for the entry through a pore. Further studies including molecular dynamics simulations are necessary to determine the possible mechanisms of enhanced accumulation of the biotinylated Atto565.